Identification of a novel linear B‐cell epitope as a vaccine candidate in the N2N3 subdomain ofStaphylococcus aureusfibronectin‐binding protein A. Issue 3 (March 2018) - Ma, Jinzhu; Wei, Yuhua; Zhang, Limeng; Wang, Xintong; Yao, Di; Liu, Daolong; Liu, Wei; Yu, Simiao; Yu, Yongzhong; Wu, Zhijun; Yu, Liquan; Zhu, Zhanbo; et al.
Abstract : Purpose. : To explore an epitope‐based vaccine against Staphylococcus aureus, we screened the epitopes in the N2N3 subdomain of fibronectin‐binding protein A (FnBPA) as a surface component of S. aureus . Methodology. : We expressed N2N3 proteins and prepared monoclonal antibodies (mAbs) against N2N3 by the hybridoma technique, before screening the B‐cell epitopes in N2N3 using a phage‐displayed random 12‐mer peptide library with these mAbs against N2N3. Finally, we analysed the characters of the screened epitopes using immunofluorescence and an S. aureus infection assay. Results. : In this paper, we identified a linear B‐cell epitope in N2N3 through screening a phage‐displayed peptide library with a 3C3 mAb against the N2N3. The 3C3 mAb recognized the 159 IETFNKANNRFSH171 sequence of the N2N3 subdomain. Subsequently, site‐directed mutagenic analysis demonstrated that residues F162, K164, N167, R168 and F169 formed the core of 159 IETFNKANNRFSH171, and this core motif was the minimal determinant of the B‐cell epitope recognized by the 3C3 mAb. The epitope 159 IETFNKANNRFSH171 showed high homology among different S. aureus strains. Moreover, this epitope was exposed on the surface of the S. aureus by using an enzyme‐linked immunosorbent assay (ELISA) assay and an indirect immunofluorescence assay. As expected, the epitope peptide evoked a protective immune response against S. aureus infection in immunized mice. Conclusion. : We identified a novel linear B‐cell epitope, 159 IETFNKANNRFSH171, in the N2N3 subdomain of S. aureus fibronectin‐binding protein A that is recognized by 3C3 mAb, which will contribute to the further study of an epitope‐based vaccine candidate against S. aureus .